Artificial inoculation methods for testing microorganisms as control agents of seed- and soil-borne Fusarium-seedling blight of maize - Eckhard Koch; Petra Zink; Tobias Pfeiffer; Astrid von Galen; Ada Linkies; Jannika Drechsel; Tim Birr (Journal of Plant Diseases and Protection, 2020)
The study describes the development and employment of plant tests based on artificial inoculation of seeds or the potting substrate for evaluating the potential of microorganisms to control seedling blight of maize caused by seed- and soil-borne fusaria. Nine strains of Fusarium were isolated from maize kernels and identified morphologically and by molecular methods as belonging to the species Fusarium verticillioides, F. subglutinans, F. cerealis, F. poae and F. proliferatum . In order to determine pathogenicity, maize kernels were inoculated by immersion in suspensions of conidia of these isolates and sown in a pasteurized substrate in seed trays. Based on plant dry weight, the isolates of F. verticillioides and F. subglutinans were more pathogenic than the other isolates. Using an isolate of F. subglutinans , the efficacy of a set of 25 potential fungal and bacterial antagonists was assessed using inoculation of maize kernels by placement in mixtures of the pathogen and the antagonists. The results obtained with this methodology indicate the potential of a number of different microorganisms applied as seed treatments, including some reported previously as biocontrol agents, to control seed-borne seedling blight of maize. In order to develop a method for the testing of biocontrol agents against soil-borne attack, isolates of F. subglutinans , F. cerealis and F poae from maize kernels together with isolates of F. avenaceum , F. culmorum and F. graminearum originating from maize silage and wheat were used to artificially inoculate the potting substrate. The results showed large differences in pathogenicity, with the most aggressive isolates belonging to F. culmorum and F. graminearum.